Enhancing Students’ Concept Understanding Through The Problem-Based Learning Model: An Experimental Study - Rafinur Asbar; Woro Hastuti; Kawuryan Sekar; Anita Ekantini; Marwan Marwan (AL-ISHLAH: Jurnal Pendidikan, 2025)
Improving students’ conceptual understanding in science remains a key challenge in higher education, particularly in teacher training programs. Problem-Based Learning (PBL) has been widely proposed as an effective model to foster deeper learning and critical thinking. This study investigates the effectiveness of the PBL model in enhancing students’ conceptual understanding in a fundamental science concepts course. A quasi-experimental design with a nonequivalent control group was employed. The study involved 78 fourth-semester students from the PGMI program at UIN Sunan Kalijaga, divided into an experimental group (PBL model) and a control group (cooperative model), each comprising 39 students. Pretest and posttest data were collected using validated essay-based instruments focused on the topic of static electricity. Data were analyzed using normality, homogeneity, and independent sample t-tests with SPSS 26. Both groups showed improvement, but the experimental class demonstrated significantly higher gains in conceptual understanding. The posttest mean score of the experimental group was 88.54 (Very High), compared to 78.72 (High) in the control group. Statistical analysis confirmed a significant difference between the groups (p = 0.00 0.05), indicating the effectiveness of the PBL model. The results support the use of PBL as a pedagogical approach to enhance science concept mastery. Given its impact, PBL is recommended for wider application in science education, though further research with diverse samples and long-term designs is suggested.